Photodynamic therapy of cervical cancer: a scoping review on the efficacy of various molecules - Nasrulla Abdullaevich Shanazarov; Afshin Zare; Nadiar Maratovich Mussin; Rustam Kuanyshbekovich Albayev; Asset Askerovich Kaliyev; Yerbolat Maratovich Iztleuov; Sandugash Bakhytbekovna Smailova; Amin Tamadon (SAGE Publishing, 2024)
Background: Cervical cancer poses a considerable worldwide health issue, where infection with the human papillomavirus (HPV) plays a vital role as a risk factor. Photodynamic therapy (PDT) is a minimally invasive treatment for HPV-related cervical lesions, which uses photosensitizers and light to selectively destroy abnormal cells. Objectives: Our objective is to present a comprehensive overview of the different types of molecules employed in PDT to reduce the occurrence and fatality rates associated with cervical cancer. Design: Scoping review and bibliometric analysis. Methods: The article explores clinical trials investigating the efficacy of PDT in treating low-grade squamous intraepithelial lesion and high-grade squamous intraepithelial lesion, as well as preclinical approaches utilizing various molecules for PDT in cervical cancer. Furthermore, the article sheds light on potential molecules for PDT enhancement, examining their properties through computer modeling simulations, molecular docking, and assessing their advantages and disadvantages. Results: Our findings demonstrate that PDT holds promise as a therapeutic approach for treating cervical lesions associated with HPV and cervical cancer. Additionally, we observe that the utilization of diverse dye classes enhances the anticancer effects of PDT. Conclusion: Among the various molecules employed in PDT, functionalized fullerene exhibits a notable inclination toward overexpressed receptors in cervical cancer cells, making it a potential candidate for intensified use in PDT. However, further research is needed to evaluate its long-term effectiveness and safety.